Motherhood As Leadership in Enabling High-Performance Organization by Nurturing Millennials in A Patriarchal Culture: A Conceptual Revisit - Irka Wijaya; Anggara Wisesa (Research Synergy Foundation, 2022)
Patriarchal culture puts women into challenging situations where they are expected to maintain role duality, balancing gender role expectations of a mother and professional work. Women, especially working mothers, overcome this by shaping their leadership style based on their acquired motherhood parenting style. Their nurturing, empowerment, empathy, and understanding may answer millennials' expectations of ideal leaders to prepare them as future leaders. Leadership influences multiple levels of an organization and performance, enabling millennials as the biggest yet most influential working cohort might be the key to achieving a high-performance state in the current dynamic yet challenging economic landscape. This paper aims to discuss how motherhood shapes leadership characteristics in working mothers, which supports millennials in enabling high-performance organizations. Based on the critical reflection selected for this study, the reflected motherhood into leadership style may be beneficial to fill the demand created by millennials to support their individual contribution, which in the end, shapes organizational culture and enables high-performance organizations. Keywords: Leadership; Millennials; Motherhood; Mentoring; Patriarchal Culture